Analyzing the Differences in Organizational Commitment and Teamwork Competence by MBTI Personality Type of Aviation Department Students - Seung Joon Jeon; Yun Sick Jung; Ri Hyun Shin (Hanggong uju uihakoeji, 2023)
Purpose: For students who have already decided on their career path by entering the aviation departments, this study aims to analyze organizational commitment and teamwork relationships using the Myers-Briggs Type Indicator (MBTI) personality type as a tool. Methods: In order to investigate the career choices of aviation workers according to MBTI personality types, a survey was conducted targeting enrolled in and graduating from the aviation departments, and organizational commitment and teawork were analyzed using SPSS WIN 21.0. Results: Sening, Feeling, and Perceiving were mainly found in students who chose cabin crew as their career, whereas students in department of flight crew and aviation maintenance showed high level in Instuition, Thinkg, and Juding. As a result of the analysis, the MBTI type for each career path of aviation students was mainly ENTP for flight crew students, ESFP for cabin crew students, and INTP for aviation maintenance students. Conclusion: Even if students make their choice based on advice, subjective and objective judgments in choosing a career path, there are cases in which the chosen job does not suit them. Therefore, it is hoped that various indicators such as the MBTI will be used to help studnes choose their career path.